Portrait of psychological well-being in individuals who have coming out as gender dysphoria - Kuway, Hana Gracya; Huwae, Arthur (Universitas Islam Negeri Ar-Raniry, 2023)
Choosing to be a gender dysphoria is quite difficult to voice yourself in behavior, expression, even in dress, good and bad responses always come. In Indonesia, it is still fairly sensitive to talk about gender deviation. Individuals who have been diagnosed as gender dysphoria by psychologists / psychiatrists could propably feel unconfortable in society. Some of them who have come out in the environment but have not been fulfilled in terms of psychological well-being due to several factors. Based on the phenomenon that occurs, researchers want to examine the portrait of psychological well-being, both through dimensions and factors in individuals who have come out as gender dysphoria. The method used in this study is qualitative descriptive phenomenology. The data collection process is carried out by using observations, interviews, and documents. Data analysis is performed using interactive data analysis methods. The results of this study show that in general gender dysphoria individuals who have come out have been fulfilled in the picture of psychological well-being for themselves and the surrounding environment, where it appears that participants have fulfilled the dimensions and factors of psychological well-being theory of Ryff and Keyes (1995). Researchers also found a new factor that affects psychological well-being, namely the self-love factor.